Air pollution emission inventory for domestic cooking and solid waste open burning in Yangon, Myanmar to assess potential co-benefits from various control scenarios - Khin Phoo Pwint Kyi; Nguyen, Thi Kim Oanh; Visvanathan, C.; Shipin, Oleg V.; Deutscher Akademishcer Austausch Dienst (DAAD); Asian Institute of Technology Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2014)
A questionnaire survey was conducted for the purpose of emission inventory for cooking and solid waste open burning in Yangon, Myanmar. Totally 720 households were surveyed out of 12 townships in the city during the period from December to February 2014. Based on the survey results, homes can be classified into 3 groups with distinctly different type of houses, kitchen location, cookstove and type of fuel used for cooking, namely LPG, charcoal and wood. The survey also included health symptoms and this study investigated the link between the health risk in different areas (urban, suburban and outskirts). The emission from residential cooking activities was quantified for the base case as of 2013 as well as the emission reduction of air pollution and climate forcing agents under different fuel-cookstove technology scenarios. The results showed that the type of primary fuel in all three areas was almost the same which is electricity that accounted for over 80% of the total fuel consumption. The types of supplemental fuels are LPG, charcoal and wood. The consumption rate varied according to the areas. The consumption of LPG and charcoal is 13.9% and 40%, respectively, in the urban area, as compared to 38.9% and 36.1% in sub-urban area. In outskirt area the consumption for LPG, charcoal and wood was 44.4%, 30.6% and 1.7%, respectively. Thus, solid fuel, as supplemental fuel, shares are still relatively high in Yangon. The emission per capita obtained for average of the current cooking fuel mixture of PM10, PM2.5, SOb2(B, COb2(B, CO, NOx, NH3, CH4, BC, OC, N2O and NMVOC was, respectively, 0.028, 0.024, 0.005, 33.303, 1.104, 0.014, 0.007, 0.057, 0.007, 0.014, 0.001 and 0.04kg per year. Total emission (tonne/year) for Yangon City of these pollutants was 90, 77, 14, 104881, 3477, 44, 21, 179, 24, 44, 5, 126, respectively. Total emission of climate forcers in study area of Yangon division, 2013, in COb2 (Bequivalent for 20-year time horizon was 188 kilo tonnes as compared to 129 kilo tonnes for 100-year time horizon. As for health risk, there were some respondents reporting as having health symptoms when exposed to smoke during cooking, especially in urban area. The health symptoms of stinging eyes and runny nose in urban area collectively shared 25% of the respondents. In sub-urban and outskirt areas, the respondents reporting of stinging eyes was 11% and 4.4 %, respectively, and in runny nose symptoms was 3.3% and 0.6%, respectively. Not more than 10% of respondents reporting symptoms related lung disease problems in the last 5 years. The air quality and climate co-benefits for various cooking-stove system scenarios for residential cooking sector in Yangon division were analyzed and quantified. Three fuel-cookstove technology scenarios were considered, including (1) base case scenario (actual situation in 2013), (2) cleaner cookstove technology with improved cookstove for charcoal scenario (S1), and (3) cleaner cookstoves and fuel technology with LPG cookstove scenario (S2). The total global warming potential of cooking for the base case, S1 and S2 were 188, 216 and 74 kilo tonnes in COb2 (Beq for 20-year horizon and 129, 123 and 64 kilo tonnes of COb2 (Beq for 100 year horizon. Compared with base case scenario, the GHGs emission (COb2 (Beq) in S1 scenarios would increase by 13 % for 20-year but reduce by 5% for 100-year time horizon. S2 scenario also showed reduction in comparison with base case, i.e. 60% for 20-year and 51% for 100-year time horizon of the total COb2 (Beq. The survey showed that the amount of solid waste subjected to backyard burning appeared to be small. However, further study is required to better quantify this emission, especially to include other types of solid waste open burning.s
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Environmental Engineering and Management
Thesis (M.Eng.) - Asian Institute of Technology, 2014
Keywords: Air -- Pollution -- Myanmar -- Yangon; Cookery -- Environmental aspects -- Myanmar -- Yangon; Air quality -- Myanmar -- Yangon